Answer :
Answer:
x= 5, y = -2
Step-by-step explanation:
-2x-9y=8
-5x-8y=-9
Multiply the first equation by 5
5( -2x-9y)=8*5
-10x -45y = 40
Multiply the second equation by -2
-2 (-5x-8y)=-9*-2
10x +16y = 18
Add the new equations together to eliminate x
-10x -45y = 40
10x +16y = 18
--------------------------
-29y = 58
Divide each side by -29
-29y/-29 = 58/-29
y = -2
Now we can find x
-2x-9y=8
-2x -9(-2) =8
-2x +18 = 8
Subtract 18 from each side
-2x+18-18 = 8-18
-2x = -10
Divide by -2
-2x/-2 = -10/-2
x = 5
Answer:
(5,-2)
Step-by-step explanation:
−2x−9y=8 (1)
-5x-8y=-9 (2)
5(1) - 2(2)
-10x - 45y = 40
10x + 16y = 18
-28y =58
y = -2
−2x−9(-2)=8
-2x = -10
x = 5